Dryness–Wetness Encounter Probabilities’ Analysis for Lake Ecological Water Replenishment Considering Non-Stationarity Effects - Xu, Yiran; Lu, Fan; Zhou, Yuyan; Ruan, Benqing; Dai, Yanyu; Wang, Kangming (Frontiers in Environmental Science, 2022)
Ecological water replenishment (EWR) via inter-basin water transfer projects has been regarded as a critical solution to reducing the risk of lake shrinkage and wetland degradation. The hydrological conditions of EWR water sources do not change synchronously which may have an impact on the transferable water. Based on the GAMLSS model and the multivariate Copula model, this work presents a research approach for EWR via inter-basin water transfer projects that can capture the nonstationarity of the runoff series and the frequency of dryness-wetness encounters, as well as speculate on various scenarios throughout the project operation phase. We present a case study on the Baiyangdian Lake, acting as the largest freshwater wetland in North China, which has suffered from severe degradation during the past decades and deserves thorough ecological restoration. The GAMLSS model was used to examine the non-stationarity characteristics of EWR water sources including the Danjiangkou Reservoir (DJK), the Huayuankou reach of the Yellow River (HYK), and upstream reservoirs (UR). The multivariate Copula model was implemented to evaluate the synchronous-asynchronous characteristics for hydrological probabilities for the multiple water sources. Results show that (1) significant nonstationarity has been detected for all water sources. Particularly, a significant decreasing trend has been found in UR and HYK. (2) The nonstationary model with time as the explanatory variable is more suitable for the runoff series of DJK, HYK and UR. Under the nonstationary framework, the wet-dry classification of runoff series is completely changed. (3) Whether the bivariate or trivariate combination types, the asynchronous probability among the three water resources is over 0.6 except DJK-HYK, which indicates the complementary relationship. Multiple water resources are necessary for EWR. What’s more, during a dry year of UR, the conditional probability that both DJK and HYK are in a dry year is 0.234. To alleviate the problem of not having enough water, some additional water resources and an acceptable EWR plan are required.